Prediction of thrusting sequence based on maximum rock strength and sandbox validation - Cubas, N.; Maillot, B.; Leroy, Y. M.; Barnes, C.; Pubellier, M. (TRABAJOS DE GEOLOGÍA, 2009)
This research aims to develop and validate simple procedures, accounting for mechanical equilibrium and maximum rock strength, to select the dominant mode of folding and to predict sequences of thrusting in fold-and-thrust belts and accretionary wedges. An inverse analysis of sandbox experiments is proposed to validate the procedures, leading to an estimation of the fault strength from the position, and the lifetime of the first thrust. The statistics of experimental uncertainties is constructed to obtain probability distributions of the friction parameters. The procedure will be applied to a real field case: the Agrio fold-and-thrust belt, Neuquén basin, Argentina.